English Tutor Perspectives on the Important Role of Continuing Professional Development (CPD) Programs in Improving Digital Skills and Pedagogical Adaptation in the Era of Digital Learning - Yunita Salsabilah; Azkia Nasywa Rana; Ashfiyah El-Ni’mah; Syaffaniyatul Qolbi; Ratna Sari Dewi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study looks at the CPD activities English language tutors undertake or ignore due to the demands of the digitally adaptive teaching. With the role of technology in teaching becoming more dominant, there is a requirement for tutors to routinely update their competencies. Data was collected through three semi-structured interviews with educators from different organizations and, subsequently, there was applied thematic analysis. The results indicated that tutors of English assume that CPD, in general, is useful because without it educators are likely to become antiquated and irrelevant, more so in an environment populated by digital natives. CPD proved to be useful when educators are able to receive direct and pragmatic training, but educators experience systemic challenges e.g. no training, inadequate knowledge, and limited funding. Support for CPD from institutions and authorities seemed deficient which created lopsided, unsatisfactory results of CPDs. The study concludes that CPD programs, in particular training for tutors, need to be more flexible and sustainable, with more focus placed on developing the digital capabilities of the educators to optimize their teaching in a digitally adaptive environment.